Seletividade do herbicida saflufenacil aplicado em pós-emergência em dez variedades de cana-de-açúcar na condição de soca - Costa, S.Í.a. [UNESP]; Martins, D. [UNESP]; Cardoso, L.a. [UNESP]; Rodrigues, A.c.p. [UNESP]; Vitorino, H.s. [UNESP]; Marques, R.p. [UNESP] (Instituto Biológico, 2012)
This study was aimed to evaluate the selectivity of the herbicide saflufenacil applied alone and mixed, in post-emergence on 10 sugarcane cultivars in the second year after planting. The experiment was carried out in Botucatu, state of São Paulo, Brazil. The experimental design was a randomized split plot with 4 replications, with the cultivars set up in the plot and the herbicides in the subplot. The treatments were: saflufenacil + Assist (0.07 kg ha-1 + 0.5 v/v); saflufenacil + Break Thru (0.140 kg ha-1 + 0.05% v/v); saflufenacil (0.280 kg ha-1) and ametryne + clomazone (2.0 + 3.0 L ha-1) applied at 49 days after first harvest, and a control without application. The plants had from 2 to 4 leaves at the application time. The cultivars were: SP83-2847, SP80-3280, RB855453, SP80-1842, SP89-1115, RB867515, PO-8862, RB855156, SP80-1816 and SP81-3250. The herbicide was applied using Teejet XR11002VS spray equipment with six spray nozzles, at 200 kPa and, 200 L ha-1 spray volume. Visual evaluations were made at 3, 7, 15, 21, 30, 45 and 60 days after application. The initial visual injuries observed in the sugarcane plants were dependent on cultivars, the herbicides and, doses tested. All chemical treatments tested were selective to the different cultivars studied, without affecting the crop and sugar production.

Este trabalho teve como objetivo avaliar a seletividade do herbicida saflufenacil de forma isolada e em mistura, aplicado em pós-emergência inicial sobre dez variedades de cana-de-açúcar em condição de cana-soca. O experimento foi instalado no Município de Botucatu, SP. O deli-neamento experimental utilizado foi o de blocos casualizados com os tratamentos dispostos em parcelas subdivididas tendo como tratamento principal as variedades de cana-de-açúcar e como tratamento secundário o herbicida saflufenacil + Assist (0,07 kg ha-1 + 0,5% v/v); saflufenacil + Break Thru (0,140 kg ha-1 + 0,05% v/v); saflufenacil (0,280 kg ha-1) e ametryne + clomazone (3,0 + 2,0 L i. a. ha-1), aplicados aos 49 dias após o corte, além de uma testemunha sem aplicação. As plantas de cana-de-açúcar encontravam-se, por ocasião da aplicação, com 2 a 4 folhas. As dez variedades utilizadas foram: SP83-2847, SP80-3280, RB855453, SP80-1842, SP89-1115, RB867515, PO8862, RB855156, SP80-1816 e SP81-3250. Para a aplicação dos herbicidas utilizou-se um pulverizador costal pressurizado a CO2 equipado com barra de aplicação com seis pontas Teejet XR11002VS, à 200 kPa no volume de aplicação de 200 L ha-1. As avaliações visuais de controle foram realizadas aos 3, 7, 15, 21, 30, 45 e 60 dias após a aplicação. As injúrias visuais inicialmente observadas nas plantas de cana-de-açúcar foram dependentes da variedade e dos herbicidas e doses testados. Todos os tratamentos químicos foram seletivos às diferentes variedades estudadas, não afetando o rendimento de colmos e açúcar.
Selectivity of the herbicide saflufenacil applied in post-emergence on ten varieties of sugarcane (Saccharum spp.) in the second year after planting
Keywords: Cana-de-açúcar; seletividade; herbicidas; Sugarcane; selectivity; herbicides